Host-Gut Microbiota Metabolic Interactions and Their Role in Precision Diagnosis and Treatment of Gastrointestinal Cancers - Chunhao Cao; Siran Yue; Aiping Lu; Chao Liang (Elsevier, 2024)
The critical role of the gut microbiome in gastrointestinal cancers is becoming increasingly clear. Imbalances in the gut microbial community, referred to as dysbiosis, are linked to increased risks for various forms of gastrointestinal cancers. Pathogens like Fusobacterium and Helicobacter pylori relate to the onset of esophageal and gastric cancers, respectively, while microbes such as Porphyromonas gingivalis and Clostridium species have been associated with a higher risk of pancreatic cancer. In colorectal cancer, bacteria such as Fusobacterium nucleatum are known to stimulate the growth of tumor cells and trigger cancer-promoting pathways. On the other hand, beneficial microbes like Bifidobacteria offer a protective effect, potentially inhibiting the development of gastrointestinal cancers. The potential for therapeutic interventions that manipulate the gut microbiome is substantial, including strategies to engineer anti-tumor metabolites and employ microbiota-based treatments. Despite the progress in understanding the influence of the microbiome on gastrointestinal cancers, significant challenges remain in identifying and understanding the precise contributions of specific microbial species and their metabolic products. This knowledge is essential for leveraging the role of the gut microbiome in the development of precise diagnostics and targeted therapies for gastrointestinal cancers.